2017
DOI: 10.3389/fphar.2017.00863
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic Variation in Over 100 Genes in Patients Receiving Acenocumarol

Abstract: Coumarins are widely prescribed worldwide, and in Mexico acenocumarol is the preferred form. It is well known that despite its efficacy, coumarins show a high variability for dose requirements. We investigated the pharmacogenetic variation of 110 genes in patients receiving acenocumarol using a targeted NGS approach. We report relevant population differentiation for variants on CYP2C8, CYP2C19, CYP4F11, CYP4F2, PROS, and GGCX, VKORC1, CYP2C18, NQO1. A higher proportion of novel-to-known variants for 10 genes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…Mexico is home to 68 genetically different ethnic groups which suggests urgency for an adequate collection, classification, and characterization of variants on genes that affect drug efficacy and safety. Published studies collect the identification and determination of allele frequencies of at least all PGKB level 1 variants in Mestizos (Cuautle-Rodriguez et al, 2014; Fricke-Galindo et al, 2014; Fricke-Galindo et al, 2016; Gonzalez-Covarrubias et al, 2017). Fewer studies have included Natives, NGs techniques, or genotype-phenotype assessments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mexico is home to 68 genetically different ethnic groups which suggests urgency for an adequate collection, classification, and characterization of variants on genes that affect drug efficacy and safety. Published studies collect the identification and determination of allele frequencies of at least all PGKB level 1 variants in Mestizos (Cuautle-Rodriguez et al, 2014; Fricke-Galindo et al, 2014; Fricke-Galindo et al, 2016; Gonzalez-Covarrubias et al, 2017). Fewer studies have included Natives, NGs techniques, or genotype-phenotype assessments.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in vitro studies of major pharmacogenes have confirmed that many rare variants do have a functional impact confirming NGS bioinformatic predictions (Matimba et al, 2009; Han et al, 2017). More limited in scope, our own work has documented the importance of variants, derived from NGS, to increase the predictive value of genotypes on the pharmacokinetics of atorvastatin (Cruz-Correa et al, 2017) and the pharmacodynamics of cumarins (Gonzalez-Covarrubias et al, 2017). Nevertheless, the collection of a comprehensive pharmacogenetic set of variation is still underway, mostly for understudied populations.…”
Section: Introductionmentioning
confidence: 99%
“…Caucasian populations require a 30% lower dose of warfarin compared to Africans due to CYP2C9 and VKORC1 polymorphisms [28][29][30] . These variants account for 35% dose variations in Europeans, ~ 30% in Mexicans 31 , and 10% in African-Americans; . For the latter two, variants on NQO1, CALU, and GGCX may complement dose variation, highlighting the fact that certain genes distinctively impact on coumarin dosing according to population stratification.…”
Section: Ethnic Differences In Pgxmentioning
confidence: 99%
“…DNA fragments were hybridized with Haloplex synthetic probes for library enrichment, and adapters were ligated by PCR. Then, library qualities for fragment size and concentration were assessed using a 2100 Bioanalyzer, as previously described 37 . Sequencing was performed using a NextSeq500 system (Illumina, USA), aiming for 200x depth coverage in paired-end reads.…”
Section: Targeted Ngsmentioning
confidence: 99%
“…A total of 1274 variants were called by both aligners, which were used for the following analyses. Variants were confirmed visually in the integrative genomic viewer IGV, and also, annotated using dbSNP version 147 37,44 .…”
Section: Bioinformatic Analysesmentioning
confidence: 99%